Accounting Control in the Zenon Papyri. - Hain, H. P. (The Accounting Review, 1966)
The article explores the presence of accounting in the Zenon papyri of the Greeks. The manuscripts give evidence of a surprisingly elaborate accounting system which had been used in Greece since the fifth century B.C. All accounts were audited, as evidenced by a sloping downstroke or a heavy dot in front of each figure. The Zenon papyri include several monthly, annual, and even triennial summaries of accounting transactions. Their most remarkable feature is the high degree of accounting control and the business-like efficiency of central management.